Politbiuro . Politbiuro . Politburo . Политбюро - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with a convicted doctor about health problems in prisons; segment on militant atheism in the USSR; segment on the art of icon painting. Contributors: Politkovskii, Aleksandr Vladimirovich (Anchor) Series description: A socio-political program produced by television company VID, aired on the First channel from 1992 to 1995. From 1993 to 1994 the program was not broadcasted due to political reasons. The program was hosted by Aleksandr Politkovskii. The program had news and weather sections presented by cartoon characters named Dmitrii Politburov and Katia. The program usually ended with the verses of the poet-satirist Vadim Dabuzhskii. Интервью с осужденным врачом о проблемах здравоохранения в местах лишения свободы; сюжет о воинственном атеизме в СССР; сюжет об иконописи. Создатели: Политковский, Александр Владимирович (Ведущий/Ведущая) Описание серии: Общественно-политическая программа телекомпании ВИД, выходившая на Первом канале с 1992 по 1995 год. С 1993 по 1994 не выходила по политическим причинам. Программу вёл Александр Политковский. В передаче были рубрики новостей и погоды, которые вели анимационные персонажи по имени Дмитрий Политбюров и Катя. Выпуски программы заканчивались куплетами поэта-сатирика Вадима Дабужского.